2021
DOI: 10.26655/jrweedsci.2021.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Weeds have developed skills to compete with cultivated plants, making the former a major problem in agricultural areas. Morning glory (Ipomoea purpurea) is an important invasive plant that, in addition to competing for nutrients, makes harvesting difficult and presents seed dormancy mechanisms in soil banks. Some plants in this group have already been reported to be tolerant or resistant to herbicides. Therefore, it is necessary to seek alternative methods of management for these plants. The present study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Hill and L.A.S. Johnson) delayed and reduced the germination of I. purpurea (Fonseca and Marques, 2021). Inoue et al (2010) also observed a significant decrease in the germination of I. grandifolia by using a hydroalcoholic extract of araticum-do-cerrado (Annona crassiflora Mart.…”
Section: Resultsmentioning
confidence: 92%
“…Hill and L.A.S. Johnson) delayed and reduced the germination of I. purpurea (Fonseca and Marques, 2021). Inoue et al (2010) also observed a significant decrease in the germination of I. grandifolia by using a hydroalcoholic extract of araticum-do-cerrado (Annona crassiflora Mart.…”
Section: Resultsmentioning
confidence: 92%